Creatine supplementation in athletes: Benefits and potential risks - Bolotte, C. P. (Journal of the Louisiana State Medical Society, 1998)
Creatine as a supplement to athletic training has been available for a number of years. Although there are proven benefits in short-term exercise, recent questions have arisen regarding side effects and safety. Many scientific studies have addressed its efficacy in certain athletic events but no deleterious effects have been proven as of yet. Still, many physicians who work closely with athletes are suggesting caution before recommending its use. The use of creatine as an ergogenic aid for athletes has risen dramatically in recent years. Estimates of its use have ranged as high as 80% to 90% in professional football players and track and field athletes. It is currently legal and, until recently, was felt to be safe with few or no negatives. However, new information has become available that may dispute the acceptance of its safety. Creatine is a nitrogenous organic compound that is synthesized in the body (primarily the kidney) from arginine, glycine, and methionine. Exogenous ingestion of rich sources, such as meat and fish, suppresses this endogenous production. In "normal" non-vegetarian diets, about 1 gm of creatine is derived from diet and 1 gm from endogenous production. Creatine is degraded into creatinine at a rate of 1-2 gm/day.